Production of extracellular alkaline proteases by Aspergillus clavatus - Tremacoldi, C. R.; Carmona, E. C. (Springer, 2005)
The production of extracellular alkaline proteases from Aspergillus clavatus was evaluated in a culture filtrate medium, with different carbon and nitrogen sources. The fungus was cultivated at three different temperatures during 10 days. The proteolytic activity was determined on casein pH 9.5 at 37degreesC. The highest alkaline proteolytic activity (38 U/ml) was verified for culture medium containing glucose and casein at 1% (w/v) as substrates, obtained from cultures developed at 25degreesC for 6 days. Cultures developed in Vogel medium with glucose at 2% (w/v) and 0.2% (w/v) NH4NO3 showed higher proteolytic activity (27 U/ml) when compared to the cultures with 1% of the same sugar. Optimum temperature was 40degreesC and the half-lives at 40, 45 and 50degreesC were 90, 25 and 18 min, respectively. Optimum pH of enzymatic activity was 9.5 and the enzyme was stable from pH 6.0 to 12.0.
Keywords: alkaline proteases; Aspergillus clavatus; optimization; protease characterization; protease production